Breaking the elastic limit of piezoelectric ceramics using nanostructures: A case study using ZnO. (December 2020) - Kim, Hoon; Yun, Seokjung; Kim, Kisun; Kim, Wonsik; Ryu, Jeongjae; Nam, Hyeon Gyun; Han, Seung Min; Jeon, Seokwoo; Hong, Seungbum
Abstract: Piezoelectric materials are suitable for haptic technology as they can convert mechanical stimuli into electrical signals and vice-versa. However, owing to their disadvantageous mechanical properties such as brittleness (in ceramics) and a low piezoelectric coefficient (in polymers), their application in haptic technology remains challenging. In this paper, we introduce a truss-like 3D hollow nanostructure using zinc oxide (ZnO) that exhibits a drastically improved elastic strain limit while maintaining a piezoelectric coefficient similar to that of single-crystal ZnO. The ZnO hollow nanostructure was fabricated using proximity field nanopatterning (PnP) and atomic layer deposition (ALD) at four different processing temperatures. The piezoelectric characteristics were analyzed through dual AC resonance tracking piezoresponse force microscopy (PFM), and the piezoelectric coefficient was measured to be up to 9.2 pm/V. The nanopillar compression test result showed that the measured elastic strain limit of approximately 10% was at least 3 times greater than the previously reported value. The extended elastic limit of the 3D hollow structure was further supported by finite element simulations. The ZnO hollow nanostructure shows excellent potential for its application to enhanced haptic devices, which mimic the human sense of touch. Graphical abstract: A 3D ZnO hollow nanostructure exhibits an improved elastic strain limit while maintaining a piezoelectric coefficient similar to that of single-crystal ZnO. This nanostructure is fabricated using atomic layer deposition at four different temperatures. The piezoelectric coefficient of ≈ 9.2 pm/V and elastic strain limit of ≈ 10% are measured by piezoresponse force microscopy and nanopillar compression test, respectively. Image 1 Highlights: We developed a 3D ZnO hollow nanostructure through atomic layer deposition and 3D nanolithography. The effective piezoelectric coefficient of 3D ZnO hollow nanostructure is close to that of a single-crystal bulk ZnO. The 3D ZnO hollow nanostructure has a high elastic strain limit of 10% which is 3 times greater than the bulk ZnO value. Our 3D hollow nanostructure can be used in enhanced haptic devices, which mimic the human sense of touch.